2009
DOI: 10.1002/cjoc.200990060
|View full text |Cite
|
Sign up to set email alerts
|

Tin(II) Chloride Dihydrate Catalyzed Groebke Condensation: An Efficient Protocol for the Synthesis of 3‐Aminoimidazo[1,2‐a]pyridines

Abstract: The ability of tin(II) chloride dihydrate as a catalyst to promote the three-component condensation reaction from a diversity of aromatic aldehydes, 2-aminopyridines and isonitriles at room temperature is described. This methodology affords a number of 3-aminoimidazo[1,2-a]pyridines in the presence of tin(II) chloride dihydrate as a new and mild Lewis acid catalyst in the multi-component reaction in reasonable yields and short reaction time without any significant optimization of the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…, in the synthesis of quinoxaline from o-phenylenediamine and benzyl is compared with the efficiencies of two solid acid catalysts cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) reported for the same reaction [21,22]. Table 4 gives the product yield in EtOH and H 2 O for each catalyst and its reusability in EtOH.…”
Section: àmentioning
confidence: 98%
See 1 more Smart Citation
“…, in the synthesis of quinoxaline from o-phenylenediamine and benzyl is compared with the efficiencies of two solid acid catalysts cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) reported for the same reaction [21,22]. Table 4 gives the product yield in EtOH and H 2 O for each catalyst and its reusability in EtOH.…”
Section: àmentioning
confidence: 98%
“…But this catalyst is acidic, hygroscopic and hazardous in nature. Ahmad shaabani et al [21,22] reported two solid acid catalyst cellulose sulfuric acid (CSA) and silica sulfuric acid (SSA) for this synthesis. Though they give good yield with reusability, preparation of these catalysts involves the evolution of HCl.…”
Section: Introductionmentioning
confidence: 99%
“…This included Brønsted acids, such as acetic acid [16], perchloric acid [14][15][16], tosylic acid [54], silicasulfuric acid [55], NH 4 Cl [50,56], clay (montmorillonite K-10) [57] and PTSA/N -hydroxysuccinimide [58]. Additionally, several Lewis acids were used, such as Sc(OTf) 3 [14][15][16], MgCl 2 [59], InCl 3 [60], ZnCl 2 [61], RuCl 3 [62], tin(II) chloride dehydrate [63], trimethylsilyl chloride (TMSCl) [65] and Yb(OTf) 3 [66]. A super paramagnetic nanoparticle of modified sulphuric acid (c-Fe 2 O 3 · SiO 2 − OSO 3 H) was also used as both straightforward and green catalyst [67].…”
Section: Variations Of the Catalyst And Solventmentioning
confidence: 99%
“…One of the most common methods is the condensation of 1,2-diamine with 1,2-dicarbonyl compounds in refluxing ethanol or acetic acid. 10 Later, many improved methods has been reported for the synthesis of various quinoxaline derivatives using the Bicatalyzed oxidative coupling, 11 microwave irradiation, 12 a solid-phase synthesis, 13 and RuCl 2 -(PPh 3 ) 3 -TEMPO, 14 MnO 2 , 15 POCl 3 , 16 zeolites, 17 iodine, 18 cerium ammonium nitrate, 19 CuSO 4 ·5H 2 O 20 and SA/MeOH, 21 Montmorillonite K-10, 22 Zn[(L)proline], 23 ionic liquid, 24 Ni-nanoparticles, 25 silica sulfuric acid, 26 NH 4 Cl 27 as catalyst. Despite the progress, the state-of-the-art for the synthesis of these compounds remains less than ideal.…”
Section: Introductionmentioning
confidence: 99%